Relatively Low HIV Infection Rates in Rural Uganda, but with High Potential for a Rise: A Cohort Study in Kayunga District, Uganda - Guwatudde, David; Wabwire-Mangen, Fred; Eller, Leigh Anne; Eller, Michael; McCutchan, Francine; Kibuuka, Hannah; Millard, Monica; Sewankambo, Nelson; Serwadda, David; Michael, Nelson; Robb, Merlin (PLoS ONE, 2009)
Few studies have been conducted in Uganda to identify and quantify the determinants of HIV-1 infection. We report results from a community-based cohort study, whose primary objectives were to determine HIV-1 prevalence, incidence, and determinants of these infections, among other objectives. Methodology: Consenting volunteers from the rural district of Kayunga in Uganda aged 15–49 years were enrolled between March and July 2006. Participants were evaluated every six months. A questionnaire that collected information on behavioral and other HIV-1 risk factors was administered, and a blood sample obtained for laboratory analysis at each study visit. Principal Findings: HIV-1 prevalence among the 2025 participants was 9.9% (95% CI = 8.6%–11.2%). By the end of 12 months of follow-up, 1689.7 person-years had been accumulated, with a median follow-up time of 11.97 months. Thirteen HIV-1 incident cases were detected giving an annual HIV-1 incidence of 0.77% (95% CI = 0.35–1.19). Prevalence of HSV-2 infection was 57% and was strongly associated with prevalent HIV-1 infection (adjusted Odds Ratio = 3.9, 95% CI = 2.50–6.17); as well as incident HIV-1 infection (adjusted Rate Ratio (RR) = 8.7, 95% CI = 1.11–67.2). The single most important behavioral characteristic associated with incident HIV infection was the number of times in the past 6 months, a participant had sex with person(s) they suspected/knew were having sex with others; attaining statistical significance at 10 times and higher (adjusted RR = 6.3, 95% CI = 1.73–23.1). By the end of 12 months of follow-up, 259 participants (13%) were lost to follow-up, 13 (0.6%) had died, and 2 (0.1%) had withdrawn consent. Conclusions: Despite relatively low HIV-1 incidence observed in this community, prevalence remains relatively high. In the presence of high prevalence of HSV-2 infection and the behavioral characteristic of having sex with more than one partner, there is potential for increase in HIV-1 incidence.
Keywords: Low HIV Infection Rates; Rural Uganda; Cohort Study; Kayunga District; Uganda